2012
DOI: 10.1002/adhm.201200233
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biocompatibility of Multiwalled Carbon Nanotubes with Sensory Neurons

Abstract: Multiwalled carbon nanotubes (MWCNTs) possess unique properties rendering them a potentially useful biomaterial for neurobiological applications such as providing nanoscale contact-guidance cues for directing axon growth within peripheral nerve repair scaffolds. The in vitro biocompatibility of MWCNTs with postnatal mouse spinal sensory neurons was assessed for this application. Cell culture medium conditioned with MWCNTs was not significantly toxic to dissociated cultures of postnatal mouse dorsal root gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Natural polymer-based scaffolds exhibit similar properties to soft tissues and ensure high bioactivity and maximum cell adhesion, but are difficult to surface engineer. On the other hand, MWNTs present rather attractive surfaces for their electrical properties but, according to Gladwin et.al 42 , for MWNTs to be used as scaffolds requires robust surface modification to enhance biocompatibility and cell adhesion. The study conducted in the current work showed excellent adhesion of neurons on O2-plasma-treated chitin/CNTs scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Natural polymer-based scaffolds exhibit similar properties to soft tissues and ensure high bioactivity and maximum cell adhesion, but are difficult to surface engineer. On the other hand, MWNTs present rather attractive surfaces for their electrical properties but, according to Gladwin et.al 42 , for MWNTs to be used as scaffolds requires robust surface modification to enhance biocompatibility and cell adhesion. The study conducted in the current work showed excellent adhesion of neurons on O2-plasma-treated chitin/CNTs scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…MWCNT could also alter the systemic immune function in mice [31][35], and individuals with pre-existing allergic inflammation may be susceptible to airway fibrosis from inhaled MWCNT [36]. Furthermore, recent observations suggest that the nervous system is vulnerable to MWCNT as well [37][39]. On the other hand, there are also reports showing no inflammation or cancer occurrence after MWCNT exposure in rats [40], [41].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst data from these preliminary studies are promising, conflicting reports of reduced neuronal viability and growth on CNTs raises uncertainty as to the suitability of CNT scaffolds for enhancing axon growth in NRCs . For example, Hu et al compared the growth of postnatal hippocampal neurons on nonfunctionalised MWCNTs with that on polyethylenimine (PEI) coated onto glass coverslips as the control substrate .…”
Section: Cnts: Potential Role In Nerve Repairmentioning
confidence: 99%
“…Compared to laminin, neurite outgrowth on CNT substrates is poor . However, functionalising CNTs with laminin can support substantially greater neurite outgrowth compared to laminin‐coated TCP or other laminin coated biomaterial controls .…”
Section: Cnts: Potential Role In Nerve Repairmentioning
confidence: 99%